Subjektivitas perempuan terhadap narasi perang dalam manga "Cocoon" karya Kyo Machiko - Dewi, Fitriana Puspita (KIRYOKU, 2024)
This study explores the portrayal of female subjectivity in relation to war in shojo manga, a genre of Japanese comics targeted mainly at adolescent girls. The examination centers on the depiction of women's perspectives and experiences during war in shojo manga, as well as how these storylines both mirror and contest conventional gender roles. Employing a qualitative methodology and drawing on Helene Cixous' theory of Ecriture feminine, this paper scrutinizes the war-themed shojo manga "Cocoon" created by Kyo Machiko. The examination reveals that the representation of war in the shojo manga adopts a feminine approach, utilizing elements like soap, uniforms, school recollections, and symbolic cocoons. Furthermore, there is a deliberate divergence from traditional masculine narratives evident in the story's exclusion of male characters and the gender fluidity of the character Mayu, which serves as a form of opposition to warfare. Consequently, shojo manga emerges as a platform that amplifies and values the voices of women within a historical and cultural backdrop largely shaped by male viewpoints.